Kajian Prioritas Infografis pada Instagram @autoimun.id sebagai Media Penyebaran Informasi Autoimun - Putu Nityantari; Athanasia Octaviani Puspita Dewi (Jurnal Ilmu Perpustakaan, 2024)
This study examines the existence of the infographic priority theory belonging to Lankow., et al in 2012 inthe infographic presentation available on Instagram @autoimun.id as a medium for disseminating autoimmune information. The purpose of this study was to determine the priority of infographics in infographic presentations on Instagram @autoimun.id. The research method applied in this study is a qualitative method with a phenomenological approach. Data collection techniques in this study used observation, semi-structured interviews, and documentation. Informants were selected using purposive sampling. The data analysis technique applied in this research is the data analysis technique concept of Miles and Huberman. The results of this study are infographic presentations on Instagram @autoimun.id containing priority infographics of attractiveness which include attractive color presentations, use of easy-to-see fonts, and harmonious design layouts; memory which includes the suitability of the content of the information with the needs of the informants and the availability of new information in the form of follow-up about autoimmune causes the informants to want to see again (recall) information on infographics on Instagram @autoimun.id; and facilities which include ease of accessibility, namely ease of access to infographics and ease of distributing infographics; as well as ease of understanding regarding the contents of infographics among informants.